Optimizacija vzaimodejstvija organov upravlenija fiziceskoj kul'tuoj v Respublike Komi - Golov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
In the contemporary society the search of the ways of optimization of the management of physical culture and sports in the Russian Federation is urgent on the regional level. For a long period of time the multiply system of management of physical culture and sports has been forming in the Republic of Komi on different levels, which composes public self-steered organizations and state institutions of general and special competence. The republic management institutions must become the institutions for physical culture, and the state institutions - the auxiliary tool and support of the peoples' activity in the field of physical culture. The coordination of the state and public management institutions and the adoption of the conforming the republican programs will allow to accelerate the process of development of mass physical culture.